1996
DOI: 10.3109/13550289609146544
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of quinolinic acid in human immunodeficiency virus-infected monocytes

Abstract: Quinolinic acid (Quin) is thought to underlie cognitive and motor dysfunctions for a variety of neurological disorders. Specifically, in human immunodeficiency virus (HIV)-associated dementia, Quin levels correlate with the degree of neurological dysfunction observed in affected individuals. Since recent data fiom our laboratories suggest that both HIV-1 infection and activation of brain macrophages are required for the development of neurotoxicity we examined Quin production during virus infection and immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Our studies confirm some of these reports of low-molecular-weight heat-and proteaseresistant excitotoxins as major HIV/MDM-associated neurotoxins, which include glutamate (Fig. 3); however, our attempts to identify products of the kynurenine metabolic pathway (quinolinic acid) in macrophages as HIV/MDM excitotoxins (Brew et al, 1995;Nottet et al, 1996) in our system thus far are inconclusive (data not shown). Nonetheless, our NMDAR studies clearly indicate that neuronal NR2A and NR2B subunit expression patterns are a major determinant of hippocampal neuronal susceptibility to HIV/MDM-associated excitotoxins.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our studies confirm some of these reports of low-molecular-weight heat-and proteaseresistant excitotoxins as major HIV/MDM-associated neurotoxins, which include glutamate (Fig. 3); however, our attempts to identify products of the kynurenine metabolic pathway (quinolinic acid) in macrophages as HIV/MDM excitotoxins (Brew et al, 1995;Nottet et al, 1996) in our system thus far are inconclusive (data not shown). Nonetheless, our NMDAR studies clearly indicate that neuronal NR2A and NR2B subunit expression patterns are a major determinant of hippocampal neuronal susceptibility to HIV/MDM-associated excitotoxins.…”
Section: Discussionsupporting
confidence: 75%
“…HIV infection of macrophages within the brain is thought to be a critical factor in triggering events leading to neuronal damage and death, and multiple studies in vitro and in vivo indicate that excitotoxicity mediated by activation of macrophages plays a major role (Brenneman et al, 1988;Heyes et al, 1989;Dreyer et al, 1990;Giulian et al, 1990;Tardieu et al, 1992;Dawson et al, 1993;Lipton, 1993;Brew et al, 1995;Nottet et al, 1996;Power et al, 1998;Jiang et al, 2001;Kaul et al, 2001;Valle et al, 2004). Some of these models use HIV-infected monocytes/macrophages as a source of neurotoxins (Heyes et al, 1989;Giulian et al, 1990;Tardieu et al, 1992;Power et al, 1998), whereas others use application of recombinant proteins to neuronal cultures (Dreyer et al, 1990;Dawson et al, 1993;Lipton, 1993;Kaul et al, 2001) to model HIV/MDM neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct measurement of QUIN in CNS tissues from HIV-infected humans at autopsy revealed higher levels in the CNS of patients with HIV encephalopathy or opportunistic infections than in patients with no clinically apparent CNS dysfunction [49]. A recent in vitro study found QUIN to be produced by HIVinfected monocytes at significantly higher levels on immune activation with lipopolysaccharide or interferon-␥, suggesting that viral infection, as well as immune activation, are key determinants of QUIN production [50]. Thus, evidence is accumulating for QUIN as a useful marker of HAD that correlates with disease progression and that may in fact be directly implicated in neurotoxicity.…”
Section: Quinmentioning
confidence: 99%
“…Activated macrophages and microglia are apparently the only cells capable of catabolizing tryptophan to quinolinic acid in the CNS (20,25). Low levels of quinolinic acid production from HIV-1-infected macrophages have been observed (30,36); however, neither the mechanism of quinolinic acid synthesis (i.e., IDO induction) nor the effect of different viral strains on the induction of IDO has been previously investigated. Although the role of strain variability in the development of ADC is unknown, it has been suggested that conservation of key amino acids in the third hypervariable region (V3) of gp120 in brain-derived HIV-1 isolates correlates with their ability to infect brain microglia/macrophages (26,32).…”
mentioning
confidence: 99%
“…Macrophages activated with HIV-1 or HIV-1 envelope glycoprotein (gp120) contribute to the production of a number of putative neurotoxins including glutamate (8), arachidonic acid metabolites (12,13), nitric oxide (12), platelet-activating factor (13), tumor necrosis factor alpha (12,13,38), and quinolinic acid (30,36). Elevated levels of quinolinic acid, in particular, have been consistently observed in vivo in the cerebrospinal fluid and brain parenchyma of patients with ADC (1,19,36).…”
mentioning
confidence: 99%